The Effectiveness of Biofloc System Cultivation with the Addition of Supplements Ginger Flour through Feed on the Growth of Tilapia - Purbomartono, Cahyono; Jejentri, Jejentri; Suwarsito, Suwarsito; Mulia, Dini Siswani (Universitas Muhammadiyah Purwokerto, 2024)
Demand for tilapia consumption cannot be fulfilled due to limited availability. Intensive cultivation is carried out by increasing the stocking density to overcome this. An increase in stocking density can lead to a decrease in water quality which in turn can inhibit growth. To overcome this problem, biofloc system cultivation is carried out with herbal supplements through feed to maintain water quality and optimal fish growth. This study aims to determine the effectiveness of the ginger diet on the growth of tilapia reared for 60 days compared to the ginger and garlic diet for 90 days with biofloc system cultivation. The study was conducted by the experimental method using a completely randomized design, with 3 treatments, 1 control, and each was repeated 4 times for 60 days. The results showed that cultivating tilapia using the biofloc system with the ginger diet for 60 days significantly increased growth, while the garlic diet for 90 days was only significant for weight gain. A ginger diet for 60 days on tilapia and 90 days on gourami with a biofloc cultivation system has the same pattern and effectiveness on growth with an optimal dose of 5.63 g kg-1 feed. The cultivation of the biofloc system was more effective with the ginger diet for 60 days compared to the ginger and garlic diet for 90 days on fish growth. This shows that biofloc cultivation for 60 days with a ginger diet is recommended for fish farming.